Antimicrobial activity of endemic Crataegus tanacetifolia (Lam.) Pers and observation of the inhibition effect on bacterial cells - Benli, Mehlika; Yigit, Nazife; Geven, Fatmaguel; Guney, Kerim; Bingol, Uemit (Wiley, 2008)
AbstractUp to now an increasing number of antibiotic‐resistant bacteria have been reported and thus new natural therapeutic agents are needed in order to eradicate these pathogens. Through the discovery of plants such as Crataegus tanacetifolia (Lam.) Pers that have antimicrobial activity, it will be possible to discover new natural drugs serving as chemotherapeutic agents for the treatment of nosocomial pathogens and take these antibiotic‐resistant bacteria under control. The objective of the present study was to determine antimicrobial activity and the activity mechanism of C. tanacetifolia plant extract. The leaves of C. tanacetifolia, which is an endemic plant, were extracted using methanol and tested against 10 bacterial and 4 yeast strains by using a drop method. It was observed that the plant extract had antibacterial effects on Bacillus subtilis, Shigella, Staphylococcus aureus, and Listeria monocytogenes among the microorganisms that were tested. Minimum inhibitory concentration (MIC) results obtained at the end of an incubation of 24 h were found to be ≥6.16 mg ml−1 for B. subtilis, <394 mg ml−1 for Shigella, and ≥3.08 mg ml−1 for L. monocytogenes and S. aureus and minimum bactericidal concentration (MBC) were found as ≥24.63 mg ml−1 for B. subtilis, ≥394 mg ml−1 for Shigella, ≥6.16 mg ml−1 for L. monocytogenes, and ≥98.5 mg ml−1 for S. aureus. According to the MBC results, it was found that the plant extract had bactericidal effects and in order to explain the activity mechanism and cell deformation of bacterial strains treated with plant extract, the scanning electron microscopy (SEM) was used. The results of SEM showed that the treated cells appeared shrunken and there was degradation of the cell walls. This study, in which the antibacterial effect of C. tanacetifolia was demonstrated, will be a base for further investigations on advanced purification and effect mechanism of action of its active compounds. Copyright © 2008 John Wiley & Sons, Ltd.
Keywords: Crataegus; antimicrobial activity; Plant Extracts; Microbial Sensitivity Tests; endemic plant; Gram-Positive Bacteria; Anti-Bacterial Agents; Plant Leaves; Yeasts; Gram-Negative Bacteria; plant extract; Microscopy, Electron, Scanning; Crataegus tanacetifolia; 3. Good health